2018
DOI: 10.3390/ijerph15071394
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hypertension in Mauritians with Normotension and Prehypertension at Baseline: A Cohort Study

Abstract: Information on the predictors of future hypertension in Mauritians with prehypertension is scant. The aim of this study was to analyze the 5-year and 11-year risk of hypertension and its predictors in people with normotension and prehypertension at baseline in Mauritius in 1987. This was a retrospective cohort study of 883 men and 1194 women of Mauritian Indian and Mauritian Creole ethnicity, aged 25–74 years old, free of hypertension at baseline in 1987 with follow-up examinations in 1992 and 1998 using the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Indeed, there was a similarity in the prevalences of normotensive or prehypertensive individuals between the two groups (Table 2). Since the 11-year hypertension risk in prehypertensive Mauritius was of 3.4 (CI: 2.7 -4.3) [24], the high prevalence of prehypertension (even in the group of hose who have never been screened) should be considered as a major public health concern in Burkina Faso where population is primarily young (30,7% of adult people aged ≥ 25-64years [25], mean was 38.5 ± 11.1 years in our study). Although the prevalence of hypertension (17%) was statistically lower never been screened participants, this rate of unknown hypertension is a substantial public concern as they may bene t from earlier antihypertensives therapy to reduce the burden of potential complications.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there was a similarity in the prevalences of normotensive or prehypertensive individuals between the two groups (Table 2). Since the 11-year hypertension risk in prehypertensive Mauritius was of 3.4 (CI: 2.7 -4.3) [24], the high prevalence of prehypertension (even in the group of hose who have never been screened) should be considered as a major public health concern in Burkina Faso where population is primarily young (30,7% of adult people aged ≥ 25-64years [25], mean was 38.5 ± 11.1 years in our study). Although the prevalence of hypertension (17%) was statistically lower never been screened participants, this rate of unknown hypertension is a substantial public concern as they may bene t from earlier antihypertensives therapy to reduce the burden of potential complications.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with PHT are more likely to develop HTN than are those whose BP is normal 7–9 . Several surveys have revealed that the prevalence of PHT may be 20% among China's general adult population and 50% among those who are middle‐aged 10,11 . Therefore, in the effort to reduce the economic and health burden associated with CVD in China, it is essential to search for the most effective predictors and risk factors for HTN and PHT.…”
Section: Introductionmentioning
confidence: 99%
“…PHT individuals were more likely to develop HTN compared with those normotension and associated with increased risk of cardiovascular diseases incidence and morbidity [8][9][10]. Several surveys revealed that the prevalence of PHT may be 20% in the general adult population and 50% in the middle-aged population [11][12]. Therefore, the effective predictors and risk factors of HTN and PHT are essential to search for reducing the cardiovascular morbidity and health burden.…”
Section: Introductionmentioning
confidence: 99%